Improved MSHA-1 algorithm with mixing method - Rogel L. Quilala; Theda Flare G. Quilala (Institute of Advanced Engineering and Science, 2021)
Abstract—Recently, a Modified SHA-1 (MSHA-1) has been proposed and claimed to have better security performance over SHA-1. However, the study showed that MSHA-1 hashing time performance was slower. In this research, an improved version of MSHA-1 was analyzed using avalanche effect and hashing time as performance measure applying 160-bit output and the mixing method to improve the diffusion rate. The diffusion results showed the improvement in the avalanche effect of the improved MSHA-1 algorithm by 51.88%, which is higher than the 50% standard to be considered secured. MSHA-1 attained 50.53% avalanche effect while SHA1 achieved only 47.03% thereby showing that the improved MSHA-1 performed better security performance by having an improvement of 9.00% over the original SHA-1 and 3.00% over MSHA-1. The improvement was also tested using 500 random string for ten trials. The improved MSHA-1 has better hashing time performance as indicated by 31.03% improvement. Hash test program has been used to test the effectiveness of the algorithm by producing 1000 hashes from random input strings and showed zero (0) duplicate hashes.